دلالة المفعول به المعرّف بـــــ (ال) في أحاديث الأربعين النووية - Ummu-Hani Abas; Azlan Shaiful Baharum; Mohd Azizul Rahman Zabidin (USIM Press, 2024)
Vol. 17 No. 1 (2021): Journal of Maʿālim al-Qurʾān wa al-Sunnah